Систематизация и интерпретация законов - Аарньо, А. (Інститут держави і права ім. В.М. Корецького НАН України, 2007)
Переклад праці А. Аарніо The Systematisation and Interpretation of Statutes. Some Thoughts on Theoretical and Practical Legal Science.